Security Management Information System at Rw 03 Kampung Bulak Wareng Jurang Mangu Timur Pondok Aren Tangerang Selatan - Dessi Amelia Pratami; Dwi Putri Haziza; Ritmaineri Ritmaineri (Journal of Investment Development, Economics and Accounting, 2025)
Rukun Warga Security Management Information System is a software created and applied in Bulak Wareng Village, Jurang Mangu Timur Village, Pondok aren Tangerang Selatan, used as a security tool for Rukun Warga which has a manual work method such as siskamling.The software that is applied is software that can provide security information in Bulak Wareng Village, Jurang Mangu Timur Pondok Aren, South Tangerang, as for how it works, namely by sounding different signs in each information conveyed to the community with speaker aids that are integrated with the software created.This software also opens up employment opportunities for young village youths who are paid periodically through the RW cash so that they can be fully responsible for the software installed.